Dampak Pembelian Dalam Game Mobile Legend Terhadap Peningkatan Keterampilan dan Keterlibatan Pemain Dengan Pengalaman Game Sebagai Variabel Moderasi - Lian Fathur Ramadhan; Octaviana Dwiningtyas; Zela Fahira Yuliana; Tengku Mohd Khairal (Dinasti Review, 2024)
This study aims to investigate the relationship between in-game purchases in Mobile Legends and the improvement of players' playing skills and the extent to which experience factors moderate the relationship between these variables. This study uses a quantitative approach. Data will be collected through an online survey with a research instrument assessment using a Likert scale. The results of the study show that there is a significant relationship between the level of Mobile Legends player involvement and the intensity of in-game purchases. Players who are more involved tend to make in-game purchases with higher frequency and spend more money in the game. The implications of these findings are profound and cover several important aspects of the gaming industry as well as digital consumer behavior research. First of all, the microtransaction pricing adjustments suggested by this study can not only increase player engagement, but also have the potential to change the business paradigm in the gaming industry as a whole. By considering factors such as player price preferences and price sensitivity, developers can design smarter and more responsive pricing strategies. This will not only increase their revenues but also create a more inclusive and sustainable gaming ecosystem.